Support for jurisdictions in Indonesia and Malaysia to transition to sustainability - Peteru, S.; Komarudin, H.; Brady, M.A. (European Forest Institute, 2022)
This study conducted by CIFOR-ICRAF (as part of the EU-funded KAMI - Sustainability of Malaysian and Indonesian palm oil - project) examines and evaluates the interventions or existing support available for jurisdictions to transition to sustainability, which includes the consideration of economic, environmental, and social aspects of a sustainable palm oil value chain that is inclusive, reduces pressure on forests/deforestation-free, protects the environment, and promotes responsible business practices. Existing support or interventions in this study are defined as any policy, program, or initiative with a stated objective of helping to transition to sustainability and operating within oil palm producing landscapes.